A comprehensive study on diesel oil bioremediation under microcosm conditions using a combined microbiological, enzymatic, mass spectrometry, and metabarcoding approach - Giovanella, Patricia [UNESP]; Taketani, Rodrigo Gouvêa; Gil-Solsona, Ruben; Saldanha, Luiz Leonardo [UNESP]; Naranjo, Samantha Beatríz Esparza [UNESP]; Sancho, Juan V.; Portolés, Tania; Andreote, Fernando Dini; Rodríguez-Mozaz, Sara; Barceló, Damià; Sette, Lara Durães [UNESP] (Springer Nature, 2023)
This study aims at the application of a marine fungal consortium (Aspergillus sclerotiorum CRM 348 and Cryptococcus laurentii CRM 707) for the bioremediation of diesel oil-contaminated soil under microcosm conditions. The impact of biostimulation (BS) and/or bioaugmentation (BA) treatments on diesel-oil biodegradation, soil quality, and the structure of the microbial community were studied. The use of the fungal consortium together with nutrients (BA/BS) resulted in a TPH (Total Petroleum Hydrocarbon) degradation 42% higher than that obtained by natural attenuation (NA) within 120 days. For the same period, a 72 to 92% removal of short-chain alkanes (C12 to C19) was obtained by BA/BS, while only 3 to 65% removal was achieved by NA. BA/BS also showed high degradation efficiency of long-chain alkanes (C20 to C24) at 120 days, reaching 90 and 92% of degradation of icosane and heneicosane, respectively. In contrast, an increase in the levels of cyclosiloxanes (characterized as bacterial bioemulsifiers and biosurfactants) was observed in the soil treated by the consortium. Conversely, the NA presented a maximum of 37% of degradation of these alkane fractions. The 5-ringed PAH benzo(a)pyrene, was removed significantly better with the BA/BS treatment than with the NA (48 vs. 38 % of biodegradation, respectively). Metabarcoding analysis revealed that BA/BS caused a decrease in the soil microbial diversity with a concomitant increase in the abundance of specific microbial groups, including hydrocarbon-degrading (bacteria and fungi) and also an enhancement in soil microbial activity. Our results highlight the great potential of this consortium for soil treatment after diesel spills, as well as the relevance of the massive sequencing, enzymatic, microbiological and GC-HRMS analyses for a better understanding of diesel bioremediation.
Keywords: Aspergillus sclerotiorum; Bioaugmentation; Biostimulation; Cryptococcus laurentii; Hydrocarbon biodegradation; Marine fungi